Harnessing the innate and adaptive immune system for tissue repair and regeneration: Considering more than macrophages - Kelly, Daniel; Dunne, Aisling (My University, 2021)
Tissue healing and regeneration is a complex, choreographed, spatiotemporal process involving a plethora of cell types, the activity of which is stringently regulated in order for effective tissue repair to ensue post injury. A number of globally prevalent conditions such as heart disease, organ failure, and severe musculoskeletal disorders require new therapeutic strategies to repair damaged or diseased tissue, particularly given an ageing population in which obesity, diabetes, and consequent tissue defects have reached epidemic proportions. This is further compounded by the lack of intrinsic healing and poor regenerative capacity of certain adult tissues. While vast progress has been made in the last decade regarding tissue regenerative strategies to direct self-healing, for example, through implantation of tissue engineered scaffolds, several challenges have hampered the clinical application of these technologies. Control of the immune response is growing as an attractive approach in regenerative medicine and it is becoming increasingly apparent that an in depth understanding of the interplay between cells of the immune system and tissue specific progenitor cells is of paramount importance. Furthermore, the integration of immunology and bioengineering promises to elevate the efficacy of biomaterial-based tissue repair and regeneration. In this review, we highlight the role played by individual immune cell subsets in tissue repair processes and describe new approaches that are being taken to direct appropriate healing outcomes via biomaterial mediated targeting of immune cell activity. STATEMENT OF SIGNIFICANCE: It is becoming increasingly apparent that controlling the immune response is as an attractive approach in regenerative medicine. Here, we propose that an in-depth understanding of immune system and tissue specific progenitor cell interactions may reveal mechanisms by which tissue healing and regeneration takes place, in addition to identifying novel therapeutic targets that could be used to enhance the tissue repair process. To date, most reviews have focused solely on macrophage subsets. This manuscript details the role of other innate and adaptive immune cells such as innate lymphoid cells (ILCs), natural killer (NK) cells and γδT cells (in addition to macrophages) in tissue healing. We also describe new approaches that are being taken to direct appropriate healing outcomes via biomaterial mediated cytokine and drug delivery.
PUBLISHED
cited By 6
Keywords: Adaptive immunity; Immune modulation; Innate immunity; Macrophage polarization; Tissue engineering; Tissue healing; Tissue regeneration